2018
DOI: 10.1039/c8ta04939d
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening of hydrophobic metal–organic frameworks for the separation of H2S and CO2 from natural gas

Abstract: A computational study is reported to screen metal–organic frameworks for H2S and CO2 separation from natural gas under humid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 50 publications
4
78
0
3
Order By: Relevance
“…To quantify separation performance, several metrics were calculated from the simulation results, including C 2 H 6 working capacity (normalΔNC2H6), C 2 H 6 /C 2 H 4 selectivity (SC2H6/C2H4), regenerability ( R ), and trade‐off between SC2H6/C2H4 and normalΔNC2H6 (TSN) 33 : SC2H6/C2H4=()xC2H6/xC2H4/()yC2H6/yC2H4 normalΔNC2H6=NC2H6adspN…”
Section: Methodsmentioning
confidence: 99%
“…To quantify separation performance, several metrics were calculated from the simulation results, including C 2 H 6 working capacity (normalΔNC2H6), C 2 H 6 /C 2 H 4 selectivity (SC2H6/C2H4), regenerability ( R ), and trade‐off between SC2H6/C2H4 and normalΔNC2H6 (TSN) 33 : SC2H6/C2H4=()xC2H6/xC2H4/()yC2H6/yC2H4 normalΔNC2H6=NC2H6adspN…”
Section: Methodsmentioning
confidence: 99%
“…Such increased responses were also observed for H 2 S on ZIF-71 covered WO 3 sensors 230 and were attributed to enhanced analyte adsorption onto the ZIF-71. 231 Besides framework composition, the pore size of MOFs 232 and zeolites 233 can also be adjusted by encapsulation of ions or nanoparticles in their pores. For instance, the selectivity of a ZnO sensor coated with ZIF-71 was tuned by incorporation of silver nanoparticles.…”
Section: Pore-size Controlmentioning
confidence: 99%
“…Here it is important to discuss the role of simulated R% values in high-throughput computational screening of MOFs. In large-scale screening of MOFs, different adsorbent performance evaluation metrics 48 such as capacity, 5,49 selectivity, 21 and the APS 22 have been used for the identification of the top adsorbents. We recently showed that focusing on MOFs having R% 4 85% and then ranking them based on APSs is a good strategy to identify the most promising MOF adsorbents since several MOFs with high selectivities suffer from low R%.…”
Section: Materials Advances Papermentioning
confidence: 99%